2020
DOI: 10.1038/s41467-020-19365-w
|View full text |Cite
|
Sign up to set email alerts
|

Optimized design of single-cell RNA sequencing experiments for cell-type-specific eQTL analysis

Abstract: Single-cell RNA-sequencing (scRNA-Seq) is a compelling approach to directly and simultaneously measure cellular composition and state, which can otherwise only be estimated by applying deconvolution methods to bulk RNA-Seq estimates. However, it has not yet become a widely used tool in population-scale analyses, due to its prohibitively high cost. Here we show that given the same budget, the statistical power of cell-type-specific expression quantitative trait loci (eQTL) mapping can be increased through low-c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 46 publications
6
43
0
Order By: Relevance
“…We found we could significantly increase power by adopting a balanced study design and obtaining 20 more samples. Given that we (and others 24,31 ) found that shallower sequencing or assaying fewer cells per sample does not generally compromise power, it is more effective for investigators to allocate these resources to obtaining more samples.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We found we could significantly increase power by adopting a balanced study design and obtaining 20 more samples. Given that we (and others 24,31 ) found that shallower sequencing or assaying fewer cells per sample does not generally compromise power, it is more effective for investigators to allocate these resources to obtaining more samples.…”
Section: Discussionmentioning
confidence: 77%
“…Current single-cell simulation strategies directly simulate individual genes and focus on estimating power to detect general differential gene expression 1923 or associations with genetic variants 2324 . These strategies are typically used to simulate small datasets ranging from 400-10,000 cells with few replicates, because sampling individual genes is slow and limits larger simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The heterogeneity of breast tumours also impacts the accuracy of measuring the ABC transporter expression levels in clinical settings. Clinically testing ABC transporters using single-cell transcriptome sequencing may allow the inference of cell type composition and a more accurate quantitation of gene transcripts in breast tumour tissues [ 92 , 93 ]. Additionally, drug resistance is usually derived from the combined activity of different ABC transporters and, presumably, many other mechanisms during cancer progression.…”
Section: The Role Of Abcb1 In Breast Cancer Chemoresistancementioning
confidence: 99%
“…14,15 Likewise, for genetic analysis (expression quantitative trait loci), the statistical power of eQTL discovery is primarily determined by the degree of genetic variation across individuals rather than the number of cells per individual. 16 Nonetheless, differential expression analysis of single-cell RNA-seq is a state-of-the-art and unbiased approach to characterize cell-type-specific transcriptomic changes.…”
Section: Backgroundsmentioning
confidence: 99%